Penerapan Metode TOPSIS Dalam Penilaian Mutu Kinerja Pegawai (Application Of Topsis Method In Employee Equality Assessment) - Sumantri Sihombing; Irfan Sudahri Damanik; Ilham Syahputra Saragih (LPPM STIKOM Tunas Bangsa, 2021)
Quality human resources (HR) can increase profits and performance that achieve targets and goals. In an organization or company one of the most influential things is employee (HR). Therefore we need a way or oversight body to assess the quality of employees in the organization while reducing the subjective assessment of employee performance quality. Employee quality assessment certainly has many assessment criteria with different priorities - so we need a method that can take into account these criteria. One method for solving multi-criteria problems is Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). TOPSIS is a way of making decisions by finding the best choice among alternatives - alternatives by calculating the proximity of alternatives with the value of an ideal solution. The study was conducted by calculating the criterion points of tupoksi and daily discipline so that it is easier to assess employee quality. The final results obtained in the form of an alternative proximity value sequence with the value of the ideal solution. from the test it can be concluded that there is an ease in making more objective decisions.